Binder material, binder composition, positive electrode sheet, secondary battery, and electric device
By providing an insulating adhesive layer formed by adhesive composed of structural units A, B, C and D on the edge of the positive electrode of the battery cell, problems such as short circuits during the manufacturing process of secondary ion batteries are solved, and higher safety is achieved and lifespan.
Patent Information
- Application Number
- CN202311027156.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-15
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-15
AI Technical Summary
During the manufacturing process, secondary ion batteries are prone to assembly short circuits, low voltage, large self-discharge and large module pressure difference. This is mainly due to foreign matter breakdown caused by sputtering of metal particles generated during laser cutting, which in turn causes short circuits.
The insulating adhesive layer is arranged at the edge of the positive electrode sheet of the battery cell, and an adhesive including structural units A, B, C and D is used to form a three-dimensional crosslinking network through hydrogen bonding to improve the wear resistance and high temperature resistance of the insulating adhesive layer. Properties to prevent metal molten bead particles from splashing and laser cutting.
It effectively avoids contact and friction between the edge of the positive electrode plate and the root of the ear, prevents short circuits, and improves the safety and life of the battery cell.
Smart Images

Figure CN119490809A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an adhesive material, an adhesive composition, a positive electrode sheet, a secondary battery and an electrical device. Background Art
[0002] As a new energy battery, secondary ion batteries (such as lithium ion secondary batteries or sodium ion secondary batteries) have the advantages of high operating voltage, high specific capacity, long charge and discharge life, and no memory effect. At the same time, the safety of secondary ion batteries has become more and more the focus of people's attention. In the daily manufacturing process of secondary ion batteries, there will be abnormal cells such as 0 resistance value in assembly short circuit test, low formation voltage, large self-discharge, and large module pressure difference. When disassembling finished batteries, it will be found that the diaphragm corresponding to the blank edge of the positive electrode of the battery cell has a breakdown point. The reason is analyzed that metal particles are generated during the laser cutting process and sputtered at the blank position, causing foreign matter to break through the diaphragm corresponding to the blank, which may cause a large pressure difference in the battery cell, and may cause a short circuit in severe cases, resulting in serious accidents; and the bending of the pole ear when the battery cell is put into the shell will cause the root of the pole ear to contact the blank edge of the positive electrode, which will also cause a short circuit problem.
[0003] To solve the above problems, providing an insulating rubber layer at the edge of the positive electrode of the battery cell is very helpful in avoiding the occurrence of the above short circuit problem. Summary of the invention
[0004] The present application provides an adhesive material, an adhesive composition, a positive electrode plate, a secondary battery and an electrical device to solve the problem of poor wear resistance of insulating glue at the edge of the positive electrode plate.
[0005] The first aspect of the present application provides an adhesive material, including an adhesive, wherein the adhesive includes a structural unit A, a structural unit B, a structural unit C and a structural unit D, at least part of the structural unit A is cross-linked with at least part of the structural unit D, wherein the structural unit A is The structural units B are each independently Any one or more of, optionally, structural unit B is The structural units C are each independently Any one of, each m1 and each m2 are independently any integer from 1 to 20, optionally, m1 are independently any integer from 2 to 12, m2 are independently any integer from 8 to 12; the structural unit D is independently Any one or more of, n1 is independently any integer from 1 to 20, optionally, n1 is any integer from 1 to 12, further optionally n1 is any integer from 1 to 6.
[0006] The structural unit B is provided by acrylonitrile monomer, which is a hard monomer and can enhance the strength of the insulating adhesive layer; the structural unit C is provided by acrylate monomers, which are soft monomers and can improve the flexibility of the insulating adhesive layer and enhance the adhesion between the insulating adhesive layer and the current collector.
[0007] The structural unit A and the structural unit D form a three-dimensional cross-linked network through hydrogen bond interaction, so that the formed insulating rubber layer has better wear resistance, can isolate the effective contact and friction between the root of the pole ear and the edge of the positive electrode sheet caused by the bending of the pole ear when the battery cell is put into the shell, and effectively control the problem of short circuit between the pole ear and the positive electrode film layer. On the other hand, the above-mentioned structural units A, C and D are polymers of acrylic monomers, in which the acrylic substances are resistant to high temperature and not easy to decompose. Therefore, the formed insulating rubber layer can prevent the collector of the positive electrode sheet from being directly cut by laser, effectively resisting the splash of metal particles, and the laser cutting in the insulating rubber layer is not easy to produce metal molten beads, which effectively alleviates the problem of metal particles splashing and penetrating the diaphragm caused by direct laser cutting of the collector; at the same time, the above-mentioned three-dimensional cross-linked network also further enhances the resistance to laser cutting, and better realizes the protection of the diaphragm.
[0008] In any embodiment of the first aspect of the present application, at least part of the structural unit A, at least part of the structural unit B, at least part of the structural unit C and at least part of the structural unit D are connected in a chain to form a first chain structure, at least part of the structural unit A, at least part of the structural unit C and at least part of the structural unit D are connected in a chain to form a second chain structure; the structural unit A in at least part of the first chain structure is cross-linked with the structural unit D in at least part of the second chain structure; and the structural unit D in at least part of the first chain structure is cross-linked with the structural unit A in at least part of the second chain structure.
[0009] The first chain structure and the second chain structure contain structural units A and D at the same time, providing more sites for the cross-linking of structural units A and D, thereby further improving the density of the formed three-dimensional network and better improving the wear resistance of the adhesive material; the first chain structure contains structural units A, structural units B, structural units C and structural units D at the same time, which is more conducive to adjusting and controlling the strength provided by the chain structure by utilizing the content of structural units B and structural units C; the second chain structure contains structural units A, structural units C and structural units D at the same time, and has better flexibility, which can be used to more flexibly adjust the content of structural units C, thereby more flexibly adjusting the bonding force of the adhesive material.
[0010] In any embodiment of the first aspect of the present application, the adhesive material satisfies any one or more of the following conditions: 1) the wear resistance of the insulating adhesive layer with a thickness of 3μm-7μm formed by the adhesive material meets the following requirements: tested by an RCA paper tape wear tester, using a 55g weight and a flat tape for 300mm and 2 turns to form an experimental area, taking n test points in the experimental area and the spacing between the test points is not less than 2cm, the number of non-leaking points in the experimental area accounts for more than 30%, where 5≤n≤100, or the area of non-leaking points in the experimental area is more than 60% of the total area of the experimental area; 2) the cohesive force of the insulating adhesive layer formed by the adhesive material is 620N / m-750N / m, which can be 660N / m-725N / m; 3) the Shore hardness of the insulating adhesive layer formed by the adhesive material is 45HA-80HA, which can be 50HA-65HA; 4) the bonding force of the insulating adhesive layer formed by the adhesive material is 30N / m-90N / m, which can be 40N / m-80N / m.
[0011] In any embodiment of the first aspect of the present application, in the adhesive, the molar ratio of the structural unit D to the structural unit A is 0.5:1-5:1, optionally 0.5:1-3:1, and further optionally 1:1-3:1; optionally, the molar content of the structural unit A is 4%-50%, optionally 4%-10%, and the molar content of the structural unit D is 1%-50%, optionally 5%-30%, and further optionally 5%-15%. Thus, the cross-linking of the structural unit A and the structural unit D is utilized as much as possible to improve the wear resistance of the insulating adhesive layer formed by the adhesive substance.
[0012] In any embodiment of the first aspect of the present application, in the adhesive, the molar ratio of the structural unit C to the structural unit B is 1:1-300:1, and can be 5:1-50:1; optionally, the molar content of the structural unit B is 0.2%-20%, and can be 1%-5%; optionally, the molar content of the structural unit C is 1%-90%, and can be 55%-90%, and can be further 75%-80%. By controlling the ratio of the structural unit B and the structural unit C, the bonding force of the adhesive material can be improved as much as possible.
[0013] In any embodiment of the first aspect of the present application, the adhesive substance further comprises an insulating filler and / or a dispersant. The carboxyl group in the adhesive substance can form a hydrogen bond with the insulating filler to improve the adhesion of the formed insulating adhesive layer.
[0014] In any embodiment of the first aspect of the present application, the weight ratio of the insulating filler, the adhesive and the dispersant is (70-90):(10-25):0.4. The insulating filler can be used to reduce costs, and the dispersant can improve the dispersion effect of the insulating filler in the adhesive and avoid the subsequent cross-linking of the adhesive, and there is enough adhesive to provide good bonding force.
[0015] In any embodiment of the first aspect of the present application, the insulating filler includes any one or more of alumina, magnesium oxide, silicon dioxide, titanium dioxide, barium titanate, aluminum nitride, silicon nitride, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, mica, talc, boehmite, zeolite, apatite, kaolin or glass powder. The hardness of the above insulating fillers is different, and the hardness of boehmite is more moderate, which can improve the stability of the insulating rubber layer and will not cause the hardness to have a negative impact on the battery diaphragm.
[0016] In any embodiment of the first aspect of the present application, the volume average particle size D of the insulating filler is V 50≤1μm. Insulating fillers within this particle size range can be completely embedded in an insulating layer of conventional thickness, thereby effectively controlling the friction of the insulating fillers on the diaphragm.
[0017] In any embodiment of the first aspect of the present application, the adhesive substance also includes a solvent; optionally, the solid content of the adhesive substance is 20%-40%; optionally, the solvent of the adhesive substance includes water; optionally, the viscosity of the adhesive substance measured at 25°C and 12rpm is 350mPa·s-900mPa·s.
[0018] The second aspect of the present application provides an adhesive composition, including an adhesive, wherein the adhesive includes a first adhesive and a second adhesive, wherein the first adhesive is a polymer, including a structural unit A, a structural unit B, a structural unit C and a structural unit D, and the second adhesive is a polymer, including a structural unit A, a structural unit C and a structural unit D, wherein the structural unit A is The structural units B are each independently Any one or more of, optionally, structural unit B is The structural unit C of the first binder and the structural unit C of the second binder are each independently Each m1 and each m2 are independently any integer from 1 to 20, for example, m1 is 1, 2, 3, 4, 5, 6, 8, 10, 12, 13, 14, 15, 16, 18 or 20, and m1 is 1, 2, 3, 4, 5, 6, 8, 10, 12, 13, 14, 15, 16, 18 or 20; optionally, m1 is independently any integer from 2 to 12, and m2 is independently any integer from 8 to 12; the structural unit D of the first adhesive and the structural unit D of the second adhesive are independently n1 is each independently any integer from 1 to 20, optionally n1 is each independently any integer from 1 to 12; further optionally n1 is each independently any integer from 1 to 6.
[0019] When the adhesive composition is applied to the positive electrode plate to prepare the insulating adhesive layer, the structural unit B in the first adhesive is provided by an acrylonitrile monomer, which is a hard monomer and can enhance the strength of the insulating adhesive layer; the structural unit C in the first adhesive and the second adhesive is provided by an acrylate monomer, which is a soft monomer and can improve the flexibility of the insulating adhesive layer and enhance the bonding force between the insulating adhesive layer and the current collector.
[0020] At the same time, on the one hand, the structural unit A in the first adhesive and the structural unit D in the second adhesive, and the structural unit D in the first adhesive and the structural unit A in the second adhesive interact through hydrogen bonds to form a three-dimensional cross-linked network, so that the formed insulating adhesive layer has better wear resistance, can isolate the effective contact and friction between the root of the pole ear and the edge of the positive electrode sheet caused by the bending of the pole ear when the battery core is put into the shell, and effectively control the problem of short circuit between the pole ear and the positive electrode film layer. On the other hand, the first adhesive and the second adhesive of the adhesive composition are polymers of acrylic monomers, and the acrylic substances therein have the properties of high temperature resistance and not easy to decompose. Therefore, the formed insulating adhesive layer can prevent the collector of the positive electrode sheet from being directly cut by laser, effectively resist the splash of metal particles, and the laser cutting in the insulating adhesive layer is not easy to produce metal molten beads, which effectively alleviates the problem of metal particles splashing and penetrating the diaphragm caused by direct laser cutting of the collector; at the same time, the above-mentioned three-dimensional cross-linked network also further enhances the resistance to laser cutting, and better realizes the protection of the diaphragm.
[0021] In any embodiment of the second aspect, the weight ratio of the first adhesive to the second adhesive is 1:2.5-1:20, and can be 1:5-1:17.5. The second adhesive is used to provide good adhesion and flexibility for the insulating adhesive layer, and an appropriate amount of the first adhesive is used to improve the strength of the insulating adhesive layer, so as to better adapt to the strength of the insulating filler in the adhesive composition and the strength of the positive electrode collector, so that the adhesion is fully exerted; and the above weight ratio is used to regulate the cross-linking network density of the insulating adhesive layer, providing sufficient network support for wear resistance and protection of the current collector.
[0022] In any embodiment of the second aspect, the first adhesive satisfies any one or more of the following conditions: 1) the molar content of structural unit A in the first adhesive is 5%-30%; 2) the molar content of structural unit B in the first adhesive is 5%-85%; 3) the molar content of structural unit C in the first adhesive is 5%-85%; 4) the molar content of structural unit D in the first adhesive is 5%-15%. The hardness of the first adhesive is adjusted by using the content of structural unit B and structural unit C to meet the hardness requirements of the insulating adhesive layer for different designs and different processing methods; the content of the above structural unit A and structural unit D is relatively small in all structural units, mainly used to form a cross-linked network with the second adhesive, and also well controls the self-crosslinking of the two in the first adhesive.
[0023] In any embodiment of the second aspect, the second adhesive satisfies any one or more of the following conditions: 1) the molar content of structural unit A in the second adhesive is 5%-10%; 2) the molar content of structural unit C in the second adhesive is 70%-85%; 3) the molar content of structural unit D in the second adhesive is 5%-20%. Structural unit C accounts for a major proportion in the second adhesive, thereby providing the second adhesive with more sufficient flexibility and adhesion, thereby improving the adhesion of the insulating adhesive layer formed by the adhesive composition to the insulating filler and the positive electrode current collector.
[0024] In any embodiment of the second aspect, the weight average molecular weight of the first adhesive is 500,000-1.5 million; further, optionally, the difference between the weight average molecular weights of the first adhesive and the second adhesive is 100,000-1.5 million. This has a good suspension effect on the insulating filler, effectively preventing the insulating filler from settling, and improving the bonding force of the insulating adhesive layer.
[0025] In any embodiment of the second aspect, the adhesive material further comprises an insulating filler and / or a dispersant. The carboxyl groups of the first adhesive and the second adhesive can form hydrogen bonds with the insulating filler to improve the adhesive force of the formed insulating adhesive layer.
[0026] In any embodiment of the second aspect of the present application, the weight ratio of the insulating filler, the adhesive and the dispersant is (70-90):(10-25):0.4. The insulating filler can be used to reduce costs, and the dispersant can improve the dispersion effect of the insulating filler in the adhesive and avoid the subsequent cross-linking of the adhesive, and there is enough adhesive to provide good bonding force.
[0027] In any embodiment of the second aspect, the insulating filler includes any one or more of alumina, magnesium oxide, silicon dioxide, titanium dioxide, barium titanate, aluminum nitride, silicon nitride, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, mica, talc, boehmite, zeolite, apatite, kaolin or glass powder; optionally, the volume average particle size D of the insulating filler is V 50≤1μm. Insulating fillers within this particle size range can be completely embedded in an insulating layer of conventional thickness, thereby effectively controlling the friction of the insulating fillers on the diaphragm.
[0028] In any embodiment of the second aspect, the dispersant includes one or more of polyacrylate compounds, fatty alcohol polyether compounds or polyether-modified siloxane compounds.
[0029] In any embodiment of the second aspect, the adhesive composition further comprises a solvent; optionally, the solid content of the adhesive composition is 20%-40%; further optionally, the solvent of the adhesive composition comprises water.
[0030] In the third aspect of the present application, a positive electrode plate is provided, comprising: a positive electrode collector, at least one side of the positive electrode collector having a positive electrode film layer area and a hollow foil area; a positive electrode film layer, arranged in the positive electrode film layer area of the positive electrode collector; an insulating adhesive layer, arranged in the hollow foil area of the positive electrode collector, wherein the insulating adhesive layer is formed by using any one of the adhesive materials of the first aspect above, or is formed by curing any one of the adhesive compositions of the second aspect above.
[0031] The insulating rubber layer has good anti-wear performance, which can isolate the effective contact and friction between the root of the pole ear and the edge of the positive electrode sheet caused by the bending of the pole ear when the battery cell is put into the shell, and effectively control the problem of short circuit between the pole ear and the positive electrode film layer. At the same time, the insulating rubber layer can prevent the current collector of the positive electrode sheet from being directly cut by the laser, effectively resisting the splash of metal particles, and the laser cutting in the insulating rubber layer is not easy to produce metal molten beads, effectively alleviating the problem of metal particles splashing and penetrating the diaphragm caused by direct laser cutting of the current collector; at the same time, the above-mentioned three-dimensional cross-linked network also further enhances the resistance to laser cutting, and better realizes the protection of the diaphragm.
[0032] In any embodiment of the third aspect, the thickness of the insulating adhesive layer is less than or equal to the thickness of the positive electrode film layer. Optionally, the thickness of the insulating adhesive layer is 3 μm-7 μm.
[0033] The fourth aspect of the present application provides a method for preparing a positive electrode plate, including a process of setting a positive electrode film layer and an insulating adhesive layer on at least one side or both sides of a positive electrode current collector, wherein the process of setting the insulating adhesive layer includes: mixing the components of any one of the adhesive compositions of the first aspect to form an adhesive solution; coating the adhesive solution on the empty foil area of the positive electrode current collector to obtain a preform with the adhesive solution; heating the preform with the adhesive solution to obtain an insulating adhesive layer, and the heating temperature is optionally 90°C-120°C to accelerate the removal rate of the solvent therein.
[0034] In any embodiment of the fourth aspect, the process of mixing the components of the adhesive composition to form a slurry comprises: mixing the dispersant in the adhesive composition with water to form a first dispersion, optionally, mixing as a first stirring, the first stirring time is 5min-30min, and the stirring speed is 200rpm-400rpm; mixing the first dispersion with the insulating filler in the adhesive composition to form a second dispersion, optionally, mixing as a second stirring, the second stirring time is 30min-120min, and the stirring speed is 1200rpm-1800rpm; mixing the second dispersion with the first adhesive in the adhesive composition to form a third dispersion, optionally, mixing as a third stirring, the third stirring time is 15min-60min, and the stirring speed is 400rpm-700rpm; mixing the third dispersion with the second adhesive in the adhesive composition to form a glue, optionally, mixing as a fourth stirring, the fourth stirring time is 5min-30min, and the stirring speed is 200rpm-400rpm.
[0035] The fifth aspect of the present application provides a secondary battery, comprising a positive electrode plate, wherein the positive electrode plate comprises any one of the positive electrode plates provided in the third aspect or a positive electrode plate prepared by any one of the preparation methods provided in the fourth aspect.
[0036] A sixth aspect of the present application provides an electrical device, including a secondary battery, wherein the secondary battery includes any one of the secondary batteries provided in the fifth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0038] Figure 1 A side view of a positive electrode plate provided in one embodiment of the present application.
[0039] Figure 2is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0040] Figure 3 yes Figure 2 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0041] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.
[0042] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0043] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0044] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0045] In the drawings, the drawings are not drawn to scale.
[0046] Description of reference numerals:
[0047] 10 positive electrode plate; 11 positive electrode current collector; 12 positive electrode film layer; 13 insulating rubber layer;
[0048] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0049] The following detailed description and drawings of the embodiments of the present application are used to illustrate the principles of the present application, but cannot be used to limit the scope of the present application, that is, the present application is not limited to the described embodiments.
[0050] Hereinafter, the embodiments of the adhesive material, adhesive composition, positive electrode sheet, secondary battery and electric device of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0051] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0052] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0053] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0054] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0055] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or comprised.
[0056] If not otherwise specified, in this application, the term "or" is inclusive. For example, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0057] [Adhesive material] Secondary ion batteries are always subject to vibration during operation. As vibration occurs, the tabs in the battery cell will move relative to each other, thus causing internal friction. However, the conventional insulating adhesive layer is not wear-resistant enough, and the relative movement of the tabs will cause coating wear and pole foil leakage, thus causing a short circuit inside the battery cell.
[0058] In order to solve the above problems, in the first embodiment of the present application, an adhesive material is provided, including an adhesive, the adhesive including a structural unit A, a structural unit B, a structural unit C and a structural unit D, at least part of the structural unit A is cross-linked with at least part of the structural unit D, wherein the structural unit A is The structural units B are each independently Any one or more of, optionally, structural unit B is The structural units C are each independently Any one of, each m1 and each m2 are independently any integer from 1 to 20, optionally, m1 are independently any integer from 2 to 12, m2 are independently any integer from 8 to 12; the structural unit D is independently Any one or more of, n1 is independently any integer from 1 to 20, optionally, n1 is any integer from 1 to 12, further optionally n1 is any integer from 1 to 6.
[0059] In the adhesive of the above-mentioned adhesive material, structural unit B is provided by acrylonitrile monomer, which is a hard monomer and can enhance the strength of the insulating adhesive layer; structural unit C is provided by acrylate monomer, which is a soft monomer and can improve the flexibility of the insulating adhesive layer and enhance the bonding force between the insulating adhesive layer and the current collector.
[0060] At the same time, the structural unit A and the structural unit D form a three-dimensional cross-linked network through hydrogen bond interaction, so that the formed insulating rubber layer has better wear resistance, can isolate the effective contact and friction between the root of the pole ear and the edge of the positive electrode sheet caused by the bending of the pole ear when the battery cell enters the shell, and effectively control the problem of short circuit between the pole ear and the positive electrode film layer. On the other hand, the above-mentioned structural units A, C and D are polymers of acrylic monomers, in which the acrylic substances have the properties of high temperature resistance and non-decomposition, so the formed insulating rubber layer can prevent the collector of the positive electrode sheet from being directly cut by laser, effectively resist the splash of metal particles, and the laser cutting in the insulating rubber layer is not easy to produce metal molten beads, which effectively alleviates the problem of metal particles splashing and penetrating the diaphragm caused by direct laser cutting of the collector; at the same time, the above-mentioned three-dimensional cross-linked network also further enhances the resistance to laser cutting, and better realizes the protection of the diaphragm.
[0061] In some embodiments, at least part of the structural unit A, at least part of the structural unit B, at least part of the structural unit C and at least part of the structural unit D are connected in a chain to form a first chain structure, and at least part of the structural unit A, at least part of the structural unit C and at least part of the structural unit D are connected in a chain to form a second chain structure; the structural unit A in at least part of the first chain structure is cross-linked with the structural unit D in at least part of the second chain structure; and the structural unit D in at least part of the first chain structure is cross-linked with the structural unit A in at least part of the second chain structure.
[0062] The first chain structure and the second chain structure contain structural units A and D at the same time, providing more sites for the cross-linking of structural units A and D, thereby further improving the density of the formed three-dimensional network and better improving the wear resistance of the adhesive material; the first chain structure contains structural units A, structural units B, structural units C and structural units D at the same time, which is more conducive to adjusting and controlling the strength provided by the chain structure by utilizing the content of structural units B and structural units C; the second chain structure contains structural units A, structural units C and structural units D at the same time, and has better flexibility, which can be used to more flexibly adjust the content of structural units C, thereby more flexibly adjusting the bonding force of the adhesive material.
[0063] In some embodiments of the present application, the adhesive material satisfies any one or more of the following conditions: 1) the wear resistance of the insulating adhesive layer with a thickness of 5 μm formed by the adhesive material meets the following requirements: tested by an RCA paper tape wear tester, using a 55g weight and a flat tape for 300mm and 2 turns to form an experimental area, taking n test points in the experimental area and the spacing between the test points is not less than 2cm, the number of non-leaking points in the experimental area accounts for more than 30%, where 5≤n≤100, or the area of non-leaking points in the experimental area is more than 60% of the total area of the experimental area; 2) the cohesive force of the insulating adhesive layer formed by the adhesive material is 620N / m-750N / m, which can be 660N / m-725N / m; 3) the Shore hardness of the insulating adhesive layer formed by the adhesive material is 45HA-80HA, which can be 50HA-65HA; 4) the bonding force of the insulating adhesive layer formed by the adhesive material is 30N / m-90N / m, which can be 40N / m-80N / m.
[0064] The test method for the above cohesion is as follows:
[0065] The adhesive substance is prepared into a slurry and then applied to the carbon-coated layer of the carbon-coated copper foil. After drying, a sample sheet is obtained, one side of the sample sheet is a copper foil surface, and the other side is a glue layer formed by the adhesive substance; the sample sheet is then cut into a sample strip with a size of 2 cm wide and 6 cm long; the copper foil surface of the sample strip is bonded to the surface of the hard substrate (steel plate) with 3M-55230H double-sided adhesive (note that there are no bubbles during the bonding process). The adhesive layer of the fixed sample strip is bonded with 3M-55230H double-sided adhesive, and the copper foil of the same size as the double-sided adhesive is covered on the surface of the double-sided adhesive (note that there are no bubbles during the bonding process). The double-sided adhesive used twice is of the same size to obtain a test sample.
[0066] Manually peel off the copper foil and double-sided adhesive tape at the first end of the test sample in a 180° direction, so that it extends 1 cm beyond the first end of the entire test sample (i.e., the second end). Fix the first end (hard substrate, carbon-coated copper foil, adhesive layer) with a fixture at one end of the tensile testing machine; fix the second end with a fixture at the other end of the tensile testing machine.
[0067] The tensile tester was set to a tensile speed of 50 mm / min and a tensile length of 100 mm for testing. The peeling force data obtained in the test is the cohesive force of the coating material.
[0068] The test method of the above hardness is as follows: the hardness of the surface of the insulating rubber layer is tested using a Shaw A hardness tester.
[0069] The test method of the above-mentioned bonding force is as follows:
[0070] Specifically:
[0071] Take the positive electrode to be tested. The appearance of the positive electrode should be good, and no defective products are allowed. Use a blade to cut a sample of the positive electrode with an insulating adhesive layer that is 20mm wide and 100-160mm long. Stick the special double-sided tape NITTO.NO5000NS on the steel plate, with a tape width of 10mm and a length of 90-150mm; fix a paper tape with a width equal to the width of the sample and a length greater than the length of the sample by 80-200mm on the double-sided tape, and set a wrinkled adhesive on the paper tape; stick the fixed-size sample cut above on the wrinkled adhesive, with the insulating adhesive layer facing down, and then use a 3kg pressure roller to roll the sample surface in the same direction three times to obtain a test sample. Fix the test sample on the testing machine, fix the end of the steel plate without the pole piece with the lower clamp, fold the paper tape upwards and fix it with the upper clamp, keep the sample axis direction consistent with the force direction, load the test machine at a peeling speed of 10mm / min until the sample breaks, stop the test, record the maximum load force as F (unit N), the sample width L = 20mm, and calculate the peel strength f1 (unit N / m) according to f1 = F / L. Peel strength is the bonding force.
[0072] In some embodiments of the present application, in the above-mentioned adhesive, the molar ratio of the structural unit D to the structural unit A is 0.5:1-5:1, such as: 0.5:1, 1:1, 1.1:1, 2:1, 2.1:1, 2.2:1, 2.5:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.2:1, 3.5:1, 3.8:1, 4:1, 4.5:1 or 5:1, which can be 0.5:1-3:1, and further 1:1-3:1; Optionally, the molar content of the structural unit A is 4%-50%, such as 4%, 4.5%, 4.8%, 5%, 5.3%, 5.5%, 6%, 6.2%, 6.4%, 6.8%, 7%, 10%, 15%, 20%, 30%, 40% or 50%, and can be 4%-10%; the molar content of the structural unit D is 1%-50%, such as 1%, 4%, 5%, 6%, 8%, 10%, 13%, 14%, 15%, 20%, 30%, 40% or 50%, and can be 5%-30%, and can be further 5%-15%. Thus, the cross-linking of the structural unit A and the structural unit D is utilized as much as possible to improve the wear resistance of the insulating adhesive layer formed by the adhesive substance.
[0073] In some embodiments of the present application, in the above-mentioned adhesive, the molar ratio of structural unit C to structural unit B is 1:1-300:1, such as: 1:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 60:1, 100:1, 150:1, 200:1, 250:1, 280:1, 290:1 or 300:1; it can be optionally 5:1-50:1; the molar content of the structural unit B is 0.2%-20%, such as 0.2%, 0.25%, 0.5%, 1%, 1.5%, 2%, 2.1%, 2.5%, 3%, 3.5%, 5%, 10%, 11%, 13%, 15% or 20%, optionally 1%-5%; optionally, the molar content of structural unit C is 1%-90%, such as 5%, 10%, 20%, 30%, 40%, 45%, 50%, 55%, 58%, 60%, 68%, 70%, 75%, 77%, 78%, 80%, 85% or 90%, optionally 55%-90%, further optionally 75%-80%. The proportion of the structural unit B and the structural unit C is controlled to improve the bonding force of the adhesive material as much as possible.
[0074] In some embodiments of the present application, the above-mentioned adhesive material also includes an insulating filler and / or a dispersant. The use of the insulating filler reduces the cost, and the dispersant promotes the dispersion effect of the insulating filler in the adhesive; and the carboxyl group of the above-mentioned structural unit A can form hydrogen bonds with the insulating filler to improve the adhesion of the formed insulating adhesive layer.
[0075] In some embodiments of the present application, the ratio of insulating filler, adhesive and dispersant can refer to the composition of conventional adhesive materials. In some embodiments, the weight ratio of insulating filler, adhesive and dispersant is (70-90):(10-25):0.4. Insulating filler can be used to reduce costs, dispersant can improve the dispersion effect of insulating filler in adhesive, avoid the subsequent cross-linking of adhesive, and there is enough adhesive to provide good bonding force.
[0076] The insulating filler can be the insulating filler commonly used in the adhesive. Considering that the adhesive composition is used in the positive electrode plate and needs to withstand laser radiation later, the insulating filler can be selected from a heat-resistant and electrochemically stable inorganic material that does not soften or melt at a temperature above 600°C, typically above 700°C, for example, above 900°C, and can insulate the positive electrode from the negative electrode.
[0077] In some embodiments, the insulating filler includes any one or more of aluminum oxide, magnesium oxide, silicon dioxide, titanium dioxide, barium titanate, aluminum nitride, silicon nitride, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, mica, talc, boehmite, zeolite, apatite, kaolin, or glass powder. The hardness of the above insulating fillers is different, and the hardness of boehmite is more moderate, which can improve the stability of the insulating glue layer and will not cause the hardness to have a negative impact on the battery separator.
[0078] In some embodiments, in order to further improve the dispersion effect of the insulating filler in the adhesive and avoid the influence of the filler particle size being too large on the diaphragm, optionally, the D of the insulating filler V 50 particle size ≤ 1 μm. The insulating filler within this particle size range can be completely embedded in the insulating layer of conventional thickness, thereby effectively controlling the friction of the insulating filler on the diaphragm. The above Dv50 represents the volume average particle size, which refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%. The test method can refer to the standard GB / T 19077-2016 and be measured using a laser particle size analyzer (such as Malvern Master Size3000).
[0079] The dispersant used for the adhesive material of the present application can be selected from conventional dispersants that are conducive to the dispersion of insulating fillers. In some embodiments, the above-mentioned dispersant includes one or more of polyacrylate compounds, fatty alcohol polyether compounds, and polyether-modified siloxane compounds, such as Chemadd-6004 of Yueyang Kaimen Water-based Additive Co., Ltd. and Elaecpure LW-10 of Dow Chemical; when no solvent is included, the packaging and transportation of the adhesive material are more convenient; when a solvent is included, the use of the adhesive material is more convenient. The viscosity of adhesive materials with different solid contents is different, the coating properties of the construction are different, and the curing conditions are also different. Those skilled in the art can select the solid content according to the construction requirements. In some embodiments, the solid content of the adhesive material is optionally 20%-40% to improve the construction and curing efficiency. Optionally, the viscosity of the adhesive material measured at 25°C and 12rpm is 550mPa·s.
[0080] In some embodiments, in order to save costs and improve the safety of the operating environment, the solvent of the adhesive material further optionally includes water, that is, a water-based adhesive is provided.
[0081] [Adhesive composition]
[0082] In a second embodiment of the present application, an adhesive composition is provided, comprising an adhesive, wherein the adhesive comprises a first adhesive and a second adhesive, the first adhesive is a polymer, comprising a structural unit A, a structural unit B, a structural unit C and a structural unit D, the second adhesive is a polymer, comprising a structural unit A, a structural unit C and a structural unit D, Among them, the structural unit A is The structural units B are each independently Any one or more of, optionally, structural unit B is The structural unit C of the first binder and the structural unit C of the second binder are each independently Each m1 and each m2 are each independently an integer of 1-20, for example, m1 is 1, 2, 3, 4, 5, 6, 8, 10, 12, 13, 14, 15, 16, 18 or 20, and m1 is 1, 2, 3, 4, 5, 6, 8, 10, 12, 13, 14, 15, 16, 18 or 20; optionally, m1 is each independently any integer of 2 to 12, and m2 is each independently any integer of 8 to 12; the structural unit D of the first adhesive and the structural unit D of the second adhesive are each independently n1 is each independently any integer from 1 to 20, for example, n1 is 1, 2, 3, 4, 5, 6, 8, 10, 12, 13, 14, 15, 16, 18 or 20, and optionally, n1 is each independently any integer from 1 to 12; further optionally, n1 is each independently any integer from 1 to 6.
[0083] When the adhesive composition is applied to the positive electrode plate to prepare the insulating adhesive layer, the structural unit B in the first adhesive is provided by an acrylonitrile monomer, which is a hard monomer and can enhance the strength of the insulating adhesive layer; the structural unit C in the first adhesive and the second adhesive is provided by an acrylate monomer, which is a soft monomer and can improve the flexibility of the insulating adhesive layer and enhance the bonding force between the insulating adhesive layer and the current collector.
[0084] At the same time, on the one hand, the structural unit A in the first adhesive and the structural unit D in the second adhesive, and the structural unit D in the first adhesive and the structural unit A in the second adhesive interact through hydrogen bonds to form a three-dimensional cross-linked network, so that the formed insulating adhesive layer has better wear resistance, can isolate the effective contact and friction between the root of the pole ear and the edge of the positive electrode sheet caused by the bending of the pole ear when the battery core is put into the shell, and effectively control the problem of short circuit between the pole ear and the positive electrode film layer. On the other hand, the first adhesive and the second adhesive of the adhesive composition are polymers of acrylic monomers, and the acrylic substances therein have the properties of high temperature resistance and not easy to decompose. Therefore, the formed insulating adhesive layer can prevent the collector of the positive electrode sheet from being directly cut by laser, effectively resist the splash of metal particles, and the laser cutting in the insulating adhesive layer is not easy to produce metal molten beads, which effectively alleviates the problem of metal particles splashing and penetrating the diaphragm caused by direct laser cutting of the collector; at the same time, the above-mentioned three-dimensional cross-linked network also further enhances the resistance to laser cutting, and better realizes the protection of the diaphragm.
[0085] In some embodiments of the present application, in order to further improve the comprehensive performance of the insulating adhesive layer formed by the adhesive composition, the weight ratio of the first adhesive and the second adhesive can be selected to be 1:2.5-1:20, such as 1:17.5, 2:17.5, 4:17.5, 1:5, 2:12.5, 2:15 or 1:10; 1:5-1:17.5 can be selected. The amount of the second adhesive is relatively large relative to the amount of the first adhesive. The first adhesive is used to provide better adhesion and flexibility for the insulating adhesive layer, and the strength of the insulating adhesive layer is improved by using an appropriate amount of the second adhesive, so as to better adapt to the strength of the insulating filler in the adhesive composition and the strength of the positive electrode collector, so that the adhesion is fully exerted; and the above-mentioned weight ratio is used to adjust the density of the cross-linked network of the insulating adhesive layer to provide sufficient network support for wear resistance and protection of the collector.
[0086] The first adhesive and the second adhesive in the adhesive composition of the present application can be polymerized by acrylic monomers and acrylic acid derivative monomers corresponding to the above structural units. The properties of the adhesives will be different if the contents of each structural unit are different. In order to adjust the properties of each adhesive and make the two adhesives work together to achieve better synergy. In some embodiments of the present application, the first adhesive is a copolymer, and the first adhesive optionally meets any one or more of the following conditions: 1) the molar content of the structural unit A in the first adhesive is 5%-30%; 2) the molar content of the structural unit B in the first adhesive is 5%-85%, which can be 5%-55%; 3) the molar content of the structural unit C in the first adhesive is 5%-85%, which can be 35%-85%; 4) the molar content of the structural unit D in the first adhesive is 5%-15%. The hardness of the first adhesive is adjusted by the content of the structural unit B and the structural unit C to meet the hardness requirements of the insulating adhesive layer for different designs and different processing methods; the content of the above structural unit A and the structural unit D is relatively small in all structural units, mainly used to form a cross-linked network with the second adhesive, and also well controls the self-crosslinking of the two in the first adhesive.
[0087] In some embodiments of the present application, the second adhesive is a copolymer, and the second adhesive optionally satisfies any one or more of the following conditions: 1) the molar content of structural unit A in the second adhesive is 5%-10%; 2) the molar content of structural unit C in the second adhesive is 70%-85%; 3) the molar content of structural unit D in the second adhesive is 5%-20%. Structural unit C accounts for the majority of the second adhesive, thereby providing the second adhesive with more sufficient flexibility and adhesion, thereby improving the adhesion of the insulating adhesive layer formed by the adhesive composition to the insulating filler and the positive electrode current collector.
[0088] The first adhesive and the second adhesive in the adhesive composition of the present application are used to bond the insulating filler and the substrate. Due to the effect of gravity, the insulating filler will settle in the adhesive solution formed by the adhesive composition. When the settling phenomenon is particularly serious, it will affect the bonding force of the insulating adhesive layer on the substrate. In some embodiments of the present application, the weight average molecular weight of the first adhesive is 500,000-1.5 million; the first adhesive with the above weight average molecular weight has a high viscosity, so it has a good suspension effect on the insulating filler, effectively preventing the settling of the insulating filler and improving the bonding force of the insulating adhesive layer.
[0089] The second adhesive has better flexibility and fluidity, and its suspension effect on insulating fillers is not as good as the first adhesive. However, the second adhesive also has the characteristics of conventional polymers, that is, its viscosity increases with the increase of molecular weight. In some embodiments, the glue formed by the adhesive composition still using the second adhesive provides sufficient fluidity for easy construction. Further, optionally, the difference in weight average molecular weight between the first adhesive and the second adhesive is 0-1.5 million. The above difference can be the difference when the weight average molecular weight of the first adhesive is greater than the weight average molecular weight of the second adhesive, or it can be the difference when the weight average molecular weight of the first adhesive is less than the weight average molecular weight of the second adhesive.
[0090] In some embodiments, the adhesive material further includes an insulating filler and / or a dispersant. The use of the insulating filler in the adhesive composition of the present application reduces the cost of the composition, and the dispersant promotes the dispersion effect of the insulating filler in the adhesive; in addition, the carboxyl group can form a hydrogen bond with the insulating filler to improve the adhesion of the formed insulating adhesive layer.
[0091] The ratio of insulating filler, adhesive and dispersant can refer to the composition of conventional adhesive composition. In some embodiments, the weight ratio of insulating filler, adhesive and dispersant is (70-90): (10-25): 0.4. Insulating filler can be used to reduce costs, dispersant can improve the dispersion effect of insulating filler in adhesive, avoid the subsequent cross-linking of adhesive, and there is enough adhesive to provide good bonding force.
[0092] The insulating filler can be the insulating filler commonly used in the adhesive. Considering that the adhesive composition is used in the positive electrode plate and needs to withstand laser radiation later, the insulating filler can be selected from a heat-resistant and electrochemically stable inorganic material that does not soften or melt at a temperature above 600°C, typically above 700°C, for example, above 900°C, and can insulate the positive electrode from the negative electrode.
[0093] In some embodiments, the insulating filler includes any one or more of aluminum oxide, magnesium oxide, silicon dioxide, titanium dioxide, barium titanate, aluminum nitride, silicon nitride, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, mica, talc, boehmite, zeolite, apatite, kaolin, or glass powder. The hardness of the insulating fillers is different, and the hardness of boehmite is more moderate, which can improve the stability of the insulating rubber layer and will not cause the hardness to have a negative impact on the battery separator.
[0094] In some embodiments, in order to further improve the dispersion effect of the insulating filler in the adhesive and avoid the influence of the filler particle size being too large on the diaphragm, optionally, the D of the insulating filler V50 Particle size ≤ 1μm. Insulating fillers within this particle size range can be completely embedded in an insulating layer of conventional thickness, thereby effectively controlling the friction of the insulating filler on the diaphragm.
[0095] The dispersant used in the adhesive composition of the present application can be selected from conventional dispersants that are conducive to the dispersion of insulating fillers. In some embodiments, the dispersant includes one or more of polyacrylate compounds, fatty alcohol polyether compounds, and polyether-modified siloxane compounds, such as Chemadd-6004 from Yueyang Kaimen Water-Based Additive Co., Ltd. and Elaecpure LW-10 from Dow Chemical.
[0096] In some embodiments, the above-mentioned adhesive composition also includes a solvent; when no solvent is included, the packaging and transportation of the adhesive composition is more convenient; when a solvent is included, the use of the adhesive composition is more convenient. The viscosity of adhesive compositions with different solid contents is different, the coating properties of the construction are different, and the curing conditions are also different. Those skilled in the art can select the solid content according to the construction requirements. In some embodiments, the solid content of the adhesive composition is optionally 20%-40% to improve the construction and curing efficiency. In some embodiments, in order to save costs and improve the safety of the operating environment, the solvent of the adhesive composition further optionally includes water, that is, a water-based adhesive is provided.
[0097] In some embodiments, the wear resistance, cohesion, hardness and adhesion of the adhesive composition also meet the requirements of the above-mentioned adhesive material, which will not be repeated here.
[0098] The first adhesive and the second adhesive used in the adhesive composition of the present application can be prepared by referring to the preparation method of the prior art or using known materials. In order to facilitate those skilled in the art to implement the present application, the following preparation method is provided for reference.
[0099] First binder: Dissolve the surfactant in water at 10-30°C, and add monomer A CH2=CHCOOH, monomer B CH2=CHCN, and monomer C CH2=CHCOO(CH2) in sequence. m1 CH3 and monomer DCH2=CHCOO(CH2) n1OH, chain transfer agent (such as n-dodecyl mercaptan), blend evenly, introduce nitrogen for deoxygenation protection, form a pre-emulsion, and heat the pre-emulsion to 80°C-90°C to obtain a pre-emulsion. A surfactant (such as dialkyl sulfosuccinate salt M-30S) is dissolved in deionized water, added to a reactor and stirred, deoxygenated with nitrogen, and heated to 80°C-90°C to obtain a reactive surfactant solution. An ammonium persulfate solution is prepared with deionized water as the first initiator solution, and the pre-emulsion and the first initiator solution are continuously added dropwise to the reactive surfactant solution in the reactor at the same time, and the addition is completed, and the acrylic acid (ester) copolymer seed solution is obtained by heat preservation. An ammonium persulfate solution is prepared with deionized water as the second initiator solution, and the concentration of the second initiator solution is greater than that of the first initiator solution. The second initiator solution is added dropwise to the acrylic acid (ester) copolymer seed solution, and the addition is continued for 100min-150min, and the addition is completed, and the temperature is kept for 1h-3h to obtain an acrylic acid (ester) copolymer solution. The acrylic acid (ester) copolymer solution in the reaction kettle is cooled to 60-70°C, cooled naturally to room temperature, and decompressed to evacuate the air. The vacuum degree in the reaction kettle is lower than 0.09 MPa, and maintained for 10-50 minutes. Then the air is released to atmospheric pressure and filtered to obtain a water-based binder emulsion. The pH is then adjusted to 7-8.
[0100] Second binder: Dissolve the surfactant in water at 10-30°C, and add monomer ACH2=CHCOOH, monomer CCH2=CHCOO(CH2) in sequence. m1 CH3, monomer D CH2=CHCOO(CH2) n1OH, chain transfer agent (such as n-dodecyl mercaptan), blend evenly, introduce nitrogen for deoxygenation protection, form pre-emulsion, heat the pre-emulsion to 80℃-90℃, and obtain pre-emulsion. Dissolve surfactant (such as dialkyl sulfosuccinate salt M-30S) in deionized water, add to the reactor and stir, use nitrogen for deoxygenation protection, heat to 80℃-90℃, and obtain reactive surfactant solution. Prepare ammonium persulfate solution with deionized water as the first initiator solution, and add the pre-emulsion and the first initiator solution to the reactive surfactant solution in the reactor at the same time, add the dropwise addition to the reactive surfactant solution in the reactor, keep warm to obtain acrylic acid (ester) copolymer seed solution. Prepare ammonium persulfate solution with deionized water as the second initiator solution, the concentration of the second initiator solution is greater than the concentration of the first initiator solution, add the second initiator solution dropwise to the acrylic acid (ester) copolymer seed solution, continue to add dropwise for 100min-150min, add dropwise addition to the reaction, keep warm for 1h-3h, and obtain acrylic acid (ester) copolymer solution. The acrylic acid (ester) copolymer solution in the reaction kettle is cooled to 60-70°C, cooled naturally to room temperature, and decompressed to evacuate the air. The vacuum degree in the reaction kettle is lower than 0.09 MPa, and maintained for 10-50 minutes. Then the air is released to atmospheric pressure and filtered to obtain a water-based binder emulsion. The pH is then adjusted to 7-8.
[0101] [Secondary battery]
[0102] Secondary batteries, also known as rechargeable batteries or storage batteries, refer to batteries that can continue to be used by recharging the active materials after the battery is discharged.
[0103] Normally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The electrolyte is between the positive electrode sheet and the negative electrode sheet, mainly to conduct active ions.
[0104] The above-mentioned adhesive composition can be considered to be applied to the position where the adhesive is needed in the secondary battery, or to be used as a raw material for a separator. In some embodiments, it is applied to the positive electrode sheet.
[0105] [Positive electrode]
[0106] like Figure 1 As shown, the positive electrode sheet 10 generally includes a positive electrode current collector 11 and a positive electrode film layer 12 disposed on at least one side of the positive electrode current collector 11 , and the positive electrode film layer 12 includes a positive electrode active material.
[0107] As an example, the positive electrode current collector 11 has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer 12 is disposed on any one or both of the two opposite surfaces of the positive electrode current collector 11 .
[0108] like Figure 1 As shown, in addition to the positive electrode film layer 12, the positive electrode current collector 11 also has an empty foil area around the positive electrode film layer 12. In some embodiments of the present application, the positive electrode plate 10 also includes an insulating adhesive layer 13, which is arranged in the empty foil area of the positive current collector 11, wherein the insulating adhesive layer 13 is cured by the adhesive composition provided in any of the above embodiments. The specific arrangement position of the insulating adhesive layer 13 in the empty foil area can be based on the prior art, such as avoiding the root of the open tab.
[0109] The insulating adhesive layer 13 in the positive electrode sheet 10 is solidified by the adhesive composition mentioned above in the present application. On the one hand, the structural unit A in the first adhesive and the structural unit D in the second adhesive, and the structural unit D in the first adhesive and the structural unit A in the second adhesive interact through hydrogen bonds to form a three-dimensional cross-linked network, so that the insulating adhesive layer has better wear resistance, can isolate the effective contact and friction between the root of the pole ear and the edge of the positive electrode sheet caused by the bending of the pole ear when the battery core is put into the shell, and effectively control the problem of short circuit between the pole ear and the positive electrode film layer. On the other hand, the first adhesive and the second adhesive of the adhesive composition are polymers of acrylic monomers, and the acrylic substances therein have the properties of high temperature resistance and not easy to decompose. Therefore, the insulating adhesive layer can prevent the current collector of the positive electrode sheet from being directly cut by laser, effectively resist the splash of metal particles, and the laser cutting in the insulating adhesive layer is not easy to produce metal molten beads, which effectively alleviates the problem of metal particles splashing and penetrating the diaphragm caused by direct laser cutting of the current collector; at the same time, the above-mentioned three-dimensional cross-linked network also further enhances the resistance to laser cutting, and better realizes the protection of the diaphragm.
[0110] In addition, the carboxyl groups of the first adhesive and the second adhesive can form hydrogen bonds with the insulating filler to improve the adhesion of the insulating adhesive layer. The structural unit B in the first adhesive is provided by acrylonitrile monomer, which is a hard monomer and can enhance the strength of the insulating adhesive layer; the structural unit C in the first adhesive and the second adhesive is provided by acrylate monomers, which are soft monomers and can improve the flexibility of the insulating adhesive layer and enhance the adhesion between the insulating adhesive layer and the current collector.
[0111] The thickness of the insulating glue layer 13 of the positive electrode sheet 10 can be based on the conventional thickness of the insulating glue layer, or the thickness can be set according to the design requirements of the battery. In some embodiments, the thickness of the insulating glue layer 13 is less than or equal to the thickness of the positive electrode film layer 12. Optionally, the thickness of the insulating glue layer 13 is 3 μm-7 μm. This can protect the positive current collector 11 and avoid increasing the volume of the battery cell due to the excessive thickness of the insulating glue layer 12.
[0112] The formation process of the above insulating adhesive layer can refer to conventional techniques, such as by coating. In some embodiments, the process of forming the insulating adhesive layer includes: mixing the adhesive composition to form an adhesive solution; coating the adhesive solution on the empty foil area of the positive electrode current collector to obtain a preform with the adhesive solution; heating the preform with the adhesive solution to obtain the insulating adhesive layer, and the heating temperature is optionally 90°C-120°C to accelerate the removal of the solvent therein.
[0113] In some embodiments, in order to improve the uniformity of mixing of the components in the adhesive composition, the process of mixing the adhesive composition to form a slurry includes:
[0114] Mixing the dispersant in the adhesive composition with water to form a first dispersion, optionally, the mixing is a first stirring, the first stirring time is 5 min-30 min, and the stirring speed is 200 rpm-400 rpm;
[0115] The first dispersion is mixed with the insulating filler in the adhesive composition to form a second dispersion. Optionally, the mixing is a second stirring, the second stirring time is 30 min-120 min, and the stirring speed is 1200 rpm-1800 rpm;
[0116] The second dispersion is mixed with the first adhesive in the adhesive composition to form a third dispersion. Optionally, the mixing is a third stirring, the third stirring time is 15 min-60 min, and the stirring speed is 400 rpm-700 rpm;
[0117] The third dispersion is mixed with the second adhesive in the adhesive composition to form an adhesive solution. Optionally, the mixing is performed as a fourth stirring process, wherein the fourth stirring process has a time of 5 min to 30 min and a stirring speed of 200 rpm to 400 rpm.
[0118] In the above process, the stirring time and speed do not need to be adjusted according to the objects to be mixed, and stirring is used to improve the mixing effect of each component.
[0119] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0120] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, when the secondary battery is a lithium-ion secondary battery, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0121] When the secondary battery is a sodium ion secondary battery, as an example, the positive electrode active material of the sodium ion secondary battery may include at least one of the following materials: at least one of a sodium transition metal oxide, a polyanionic compound, and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.
[0122] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1.
[0123] As an optional technical solution of the present application, the polyanionic compound can be a compound having sodium ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si; n represents (YO4) n- valence state.
[0124] Polyanionic compounds can also be those with sodium ions, transition metal ions, tetrahedral (YO4) n- A class of compounds containing anion units and halogen anions. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si, and n represents (YO4) n- valence state; the halogen may be at least one of F, Cl and Br.
[0125] Polyanionic compounds can also be sodium ions, tetrahedral (YO4) n- Anion unit, polyhedral unit (ZO y ) m+ and an optional halogen anion. Y can be at least one of P, S and Si, and n represents (YO4) n- valence state; Z represents a transition metal, which may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; m represents (ZO y ) m+ valence state; the halogen may be at least one of F, Cl and Br.
[0126] Polyanionic compounds include NaFePO4, Na3V2(PO4) (sodium vanadium phosphate, NVP for short), Na4Fe3(PO4)2 (P2O7), NaM'PO4F (M' is one or more of V, Fe, Mn and Ni) and Na3(VO y )2(PO4)2F 3-2y At least one of (0≤y≤1).
[0127] The Prussian blue compound may be a compound having sodium ions, transition metal ions and cyanide ions (CN-). The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The Prussian blue compound may be, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.
[0128] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0129] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0130] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0131] [Negative electrode]
[0132] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0133] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0134] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0135] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0136] In some embodiments, the negative electrode film layer may further include a binder. As an example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0137] In some embodiments, the negative electrode film layer may further include a conductive agent. As an example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0138] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0139] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0140] [Electrolytes]
[0141] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0142] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.
[0143] In some embodiments, the electrolyte salt for lithium ion secondary battery may include lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate or lithium tetrafluorooxalate phosphate. The electrolyte salt for sodium ion secondary battery may include sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium hexafluoroarsenate (NaAsF6), sodium trifluoroacetate (CF3COONa), sodium trifluoromethanesulfonate (CF3NaO3S, NaOTf) or sodium tetraphenylborate (NaBPh4) One or more.
[0144] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0145] In some embodiments, the electrolyte may further include additives. As examples, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0146] [Isolation film]
[0147] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0148] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0149] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0150] In some embodiments, the secondary battery includes a secondary battery cell, or includes a battery module and a battery pack.
[0151] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0152] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0153] The present application has no particular limitation on the shape of the secondary battery cell, which may be cylindrical, square or any other shape. Figure 2 The secondary battery cell 5 is a square structure as an example.
[0154] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0155] In some embodiments, secondary battery cells may be assembled into a battery module. The number of secondary battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0156] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of secondary battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary battery cells 5 may be fixed by fasteners.
[0157] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary battery cells 5 are received in the receiving space.
[0158] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0159] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0160] In addition, the present application also provides an electric device, which includes a secondary battery provided in the present application. The secondary battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0161] As the electrical device, a secondary battery cell, a battery module or a battery pack may be selected according to its usage requirements.
[0162] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0163] [Example]
[0164] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0165] The first binder (structural unit B is ) is prepared as follows:
[0166] At a working temperature of 20°C, 5.4 g of reactive surfactant containing double bond group of dialkyl sulfosuccinate salt M-30S was dissolved in 62 g of deionized water, and monomer A CH2=CHCOOH, monomer B CH2=CHCN, monomer C CH2=CHCOO(CH2) were added in sequence. m1 CH3 and monomer D CH2=CHCOO(CH2) n1 OH, chain transfer agent n-dodecyl mercaptan 0.058g, rotation speed 350rpm, 25min blending, during which nitrogen protection, flow rate 110mL / min, forming a pre-emulsion, the pre-emulsion is heated to 85℃ at a heating rate of 2℃ / min, and kept warm for 30min to obtain a pre-emulsion. 3.8g of reactive surfactant containing double bond group dialkyl sulfosuccinate salt M-30S is dissolved in 61.3g of deionized water and added to the reactor, the rotation speed is 300rpm, nitrogen deoxygenation protection is used, the flow rate is 100mL / min, and the temperature is increased to 88℃ at a heating rate of 2℃ / min, and kept warm for 30min to obtain a reactive surfactant solution. 3.5g of ammonium persulfate solution is prepared with deionized water as the first initiator solution, and the pre-emulsion and the first initiator solution are continuously added dropwise to the reactive surfactant solution in the reactor at the same time, and the addition is completed in 160min, and the seed solution is obtained by keeping warm for 0.5h. 1.0g ammonium persulfate initiator solution was prepared with deionized water as the second initiator solution, and the second initiator solution was added dropwise to the seed solution for 120 minutes. After the addition was completed, the solution was kept warm for 2 hours to obtain an acrylic acid (ester) copolymer solution. The acrylic acid (ester) copolymer in the reactor was cooled to 65°C at a rate of 2°C / min, kept warm for 30 minutes, cooled naturally to room temperature, and decompressed to evacuate the air. The vacuum degree in the reactor was lower than 0.09 MPa, and maintained for 30 minutes. Then, the air was vented to atmospheric pressure and filtered through a 300-mesh filter cloth to obtain a second adhesive emulsion with a solid content of 50%. The pH value was then adjusted to 7-8. The solid content of the first adhesive was 15%.
[0167] The composition of the first adhesive was adjusted by adjusting the composition or amount of each monomer, and the compositions of the first adhesive 1 to the first adhesive 21 obtained are recorded in Table 1-1.
[0168] The first adhesive 22 (structural unit B is ) is prepared as follows:
[0169] At a working temperature of 20°C, 5.4 g of reactive surfactant containing double bond group of dialkyl sulfosuccinate salt M-30S was dissolved in 62 g of deionized water, and monomer A CH2=CHCOOH, monomer B styrene, monomer C CH2=CHCOO(CH2) were added in sequence. m1 CH3 and monomer D CH2=CHCOO(CH2)n1 OH, chain transfer agent n-dodecyl mercaptan 0.058g, rotation speed 350rpm, 25min blending, during which nitrogen protection, flow rate 110mL / min, forming a pre-emulsion, the pre-emulsion is heated to 85℃ at a heating rate of 2℃ / min, and kept warm for 30min to obtain a pre-emulsion. 3.8g of reactive surfactant containing double bond group dialkyl sulfosuccinate salt M-30S is dissolved in 61.3g of deionized water and added to the reactor, the rotation speed is 300rpm, nitrogen deoxygenation protection is used, the flow rate is 100mL / min, and the temperature is increased to 88℃ at a heating rate of 2℃ / min, and kept warm for 30min to obtain a reactive surfactant solution. 3.5g of ammonium persulfate solution is prepared with deionized water as the first initiator solution, and the pre-emulsion and the first initiator solution are continuously added dropwise to the reactive surfactant solution in the reactor at the same time, and the addition is completed in 160min, and the seed solution is obtained by keeping warm for 0.5h. 1.0g ammonium persulfate initiator solution was prepared with deionized water as the second initiator solution, and the second initiator solution was added dropwise to the seed solution for 120 minutes. After the addition was completed, the solution was kept warm for 2 hours to obtain an acrylic acid (ester) copolymer solution. The acrylic acid (ester) copolymer in the reactor was cooled to 65°C at a rate of 2°C / min, kept warm for 30 minutes, cooled naturally to room temperature, and decompressed to evacuate the air. The vacuum degree in the reactor was lower than 0.09 MPa, and maintained for 30 minutes. Then, the air was vented to atmospheric pressure and filtered through a 300-mesh filter cloth to obtain a second adhesive emulsion with a solid content of 50%. The pH value was then adjusted to 7-8. The solid content of the first adhesive was 15%.
[0170] The first adhesive 23 (structural unit B is ) is prepared as follows:
[0171] At a working temperature of 20°C, 5.4 g of reactive surfactant containing double bond group of dialkyl sulfosuccinate salt M-30S was dissolved in 62 g of deionized water, and monomer A CH2=CHCOOH, monomer B methyl methacrylate, monomer C CH2=CHCOO(CH2) were added in sequence. m1 CH3 and monomer D CH2=CHCOO(CH2) n1OH, chain transfer agent n-dodecyl mercaptan 0.058g, rotation speed 350rpm, 25min blending, during which nitrogen protection, flow rate 110mL / min, forming a pre-emulsion, the pre-emulsion is heated to 85℃ at a heating rate of 2℃ / min, and kept warm for 30min to obtain a pre-emulsion. 3.8g of reactive surfactant containing double bond group dialkyl sulfosuccinate salt M-30S is dissolved in 61.3g of deionized water and added to the reactor, the rotation speed is 300rpm, nitrogen deoxygenation protection is used, the flow rate is 100mL / min, and the temperature is increased to 88℃ at a heating rate of 2℃ / min, and kept warm for 30min to obtain a reactive surfactant solution. 3.5g of ammonium persulfate solution is prepared with deionized water as the first initiator solution, and the pre-emulsion and the first initiator solution are continuously added dropwise to the reactive surfactant solution in the reactor at the same time, and the addition is completed in 160min, and the seed solution is obtained by keeping warm for 0.5h. 1.0g ammonium persulfate initiator solution was prepared with deionized water as the second initiator solution, and the second initiator solution was added dropwise to the seed solution for 120 minutes. After the addition was completed, the solution was kept warm for 2 hours to obtain an acrylic acid (ester) copolymer solution. The acrylic acid (ester) copolymer in the reactor was cooled to 65°C at a rate of 2°C / min, kept warm for 30 minutes, cooled naturally to room temperature, and decompressed to evacuate the air. The vacuum degree in the reactor was lower than 0.09 MPa, and maintained for 30 minutes. Then, the air was vented to atmospheric pressure and filtered through a 300-mesh filter cloth to obtain a second adhesive emulsion with a solid content of 50%. The pH value was then adjusted to 7-8. The solid content of the first adhesive was 15%.
[0172] First adhesive 24 (structural unit C is lauryl methacrylate CH3CH2=CHCOO(CH2) 12 CH3) is prepared as follows:
[0173] At a working temperature of 20°C, 5.4 g of reactive surfactant containing double bond group of dialkyl sulfosuccinate salt M-30S was dissolved in 62 g of deionized water, and monomer A CH2=CHCOOH, monomer B CH2=CHCN, monomer C CH3CH2=CHCOO(CH2) were added in sequence. 12 CH3 and monomer D CH2=CHCOO(CH2) n1OH, chain transfer agent n-dodecyl mercaptan 0.058g, rotation speed 350rpm, 25min blending, during which nitrogen protection, flow rate 110mL / min, forming a pre-emulsion, the pre-emulsion is heated to 85℃ at a heating rate of 2℃ / min, and kept warm for 30min to obtain a pre-emulsion. 3.8g of reactive surfactant containing double bond group dialkyl sulfosuccinate salt M-30S is dissolved in 61.3g of deionized water and added to the reactor, the rotation speed is 300rpm, nitrogen deoxygenation protection is used, the flow rate is 100mL / min, and the temperature is increased to 88℃ at a heating rate of 2℃ / min, and kept warm for 30min to obtain a reactive surfactant solution. 3.5g of ammonium persulfate solution is prepared with deionized water as the first initiator solution, and the pre-emulsion and the first initiator solution are continuously added dropwise to the reactive surfactant solution in the reactor at the same time, and the addition is completed in 160min, and the seed solution is obtained by keeping warm for 0.5h. 1.0g ammonium persulfate initiator solution was prepared with deionized water as the second initiator solution, and the second initiator solution was added dropwise to the seed solution for 120 minutes. After the addition was completed, the solution was kept warm for 2 hours to obtain an acrylic acid (ester) copolymer solution. The acrylic acid (ester) copolymer in the reactor was cooled to 65°C at a rate of 2°C / min, kept warm for 30 minutes, cooled naturally to room temperature, and decompressed to evacuate the air. The vacuum degree in the reactor was lower than 0.09 MPa, and maintained for 30 minutes. Then, the air was vented to atmospheric pressure and filtered through a 300-mesh filter cloth to obtain a second adhesive emulsion with a solid content of 50%. The pH value was then adjusted to 7-8. The solid content of the first adhesive was 15%.
[0174] Table 1-1
[0175] The molecular weights in Table 1-1 are weight average molecular weights rounded to the nearest ten thousand. The test method can refer to the standard GB / T21863-2008 and be measured using an ultra-high performance polymer chromatograph.
[0176] The preparation process of the second adhesive is as follows:
[0177] At a working temperature of 20°C, 4.2 g (4.2%) of the reactive surfactant containing double bond groups of dialkyl sulfosuccinate salt M-30S was dissolved in 58 g (116%) of deionized water, and monomer A CH2=CHCOOH, monomer CCH2=CHCOO(CH2) were added in sequence. m1 CH3, monomer D CH2=CHCOO(CH2) n1OH, chain transfer agent n-dodecyl mercaptan 0.048g (0.096%), the rotation speed is 300rpm, 30min blending, during which nitrogen is introduced for deoxygenation protection, the flow rate is 100mL / min, to form a pre-emulsion, the pre-emulsion is heated to 85°C at a heating rate of 2°C / min, and the temperature is kept for 30min to obtain a pre-emulsion. 2.8g (2.8%) of the reactive surfactant containing double bond group dialkyl sulfosuccinate salt M-30S is dissolved in 51.3g (102.6%) of deionized water, added to the reactor, the rotation speed is 300rpm, nitrogen is used for deoxygenation protection, the flow rate is 100mL / min, the temperature is raised to 86°C at a heating rate of 2°C / min, and the temperature is kept for 30min to obtain a reactive surfactant solution. 3g (0.15wt%) ammonium persulfate solution was prepared with deionized water as the first initiator solution. The pre-emulsion and the first initiator solution were simultaneously and continuously added dropwise to the reactive surfactant solution in the reactor. The addition was completed over 150 minutes and the mixture was kept warm for 0.5 hours to obtain an acrylic acid (ester) copolymer seed solution. 1.0g (0.1wt%) ammonium persulfate initiator solution was prepared with deionized water as the second initiator solution. The second initiator solution was added dropwise to the acrylic acid (ester) copolymer seed solution. The mixture was continuously added dropwise for 120 minutes and the addition was completed. The mixture was kept warm for 2 hours to obtain an acrylic acid (ester) copolymer solution. The acrylic acid (ester) copolymer in the reactor was cooled to 65°C at a rate of 2°C / min, kept warm for 30 minutes, cooled naturally to room temperature, and decompressed to evacuate the air. The vacuum degree in the reactor was lower than 0.09 MPa and maintained for 30 minutes. Then the air was vented to atmospheric pressure and filtered through a 300-mesh filter cloth to obtain a second adhesive emulsion with a solid content of 50%. The pH value was then adjusted to 7-8.
[0178] The composition of the second adhesive was adjusted by adjusting the composition and amount of each monomer, and the compositions of the obtained second adhesives 1 to 12 are recorded in Table 1-2.
[0179] Table 1-2
[0180] The molecular weights in Table 1-2 are weight average molecular weights rounded to the nearest ten thousand. The test method can refer to the standard GB / T21863-2008 and be measured using an ultra-high performance polymer chromatograph.
[0181] Example 1
[0182] The dispersant was added into deionized water, and the mixture was dispersed and stirred at 300 rpm for 15 min to obtain a first dispersion;
[0183] Add the insulating filler into the first dispersion, and stir at 1500 rpm for 75 minutes to obtain a second dispersion;
[0184] Add the first adhesive emulsion into the second dispersion, and stir at 1500 rpm for 60 minutes to obtain a third dispersion;
[0185] The second adhesive latex was added to the third dispersion liquid, and dispersed at 500 rpm for 60 min to obtain an adhesive solution. The specific materials and amounts of the dispersant, insulating filler, first adhesive and second adhesive used are recorded in Table 2.
[0186] Embodiments 2 to 47:
[0187] The corresponding glue solution was prepared by referring to the process of Example 1. The specific substances and amounts of the dispersant, insulating filler, first adhesive (dry matter) and second adhesive (dry matter) used in each example are recorded in Table 2.
[0188] Comparative Example 1
[0189] The dispersant was added into deionized water, and the mixture was dispersed and stirred at 300 rpm for 15 min to obtain a first dispersion;
[0190] Add the insulating filler into the first dispersion, and stir at 1500 rpm for 75 minutes to obtain a second dispersion;
[0191] The first adhesive emulsion was added to the above dispersion, and the mixture was dispersed and stirred at 1500 rpm for 60 min to obtain an adhesive solution. The specific materials and amounts of the dispersant, insulating filler and the first adhesive used are recorded in Table 2.
[0192] Comparative Example 2
[0193] The dispersant was added into deionized water, and the mixture was dispersed and stirred at 300 rpm for 15 min to obtain a first dispersion;
[0194] Add the insulating filler into the first dispersion, and stir at 1500 rpm for 75 minutes to obtain a second dispersion;
[0195] The second adhesive emulsion was added into the second dispersion liquid, and the mixture was dispersed and stirred at 1500 rpm for 60 min to obtain a glue solution.
[0196] The specific materials and amounts of the dispersant, insulating filler and second adhesive used are recorded in Table 2.
[0197] The dispersant used in each embodiment and comparative example is Chemadd-6004 produced by Yueyang Kaimen Water-Based Additive Co., Ltd., with a mass fraction of 0.4 parts.
[0199] Viscosity test: The rotational viscosity of the glue was tested at 25°C and 12 rpm. The results are recorded in Table 3.
[0200] Abrasion resistance test: Use a 5μm scraper to scrape each of the above adhesives onto a 13μm aluminum foil, transfer to a 100°C oven for drying, and prepare the insulating adhesive layer to be tested.
[0201] RCA paper tape wear tester (BGD 530, BGD Precision Instrument (Guangzhou) Co., Ltd.); Test principle: The motor drives the paper tape to pass through an area on the surface of the test sample at a uniform speed and applies a certain pressure to wear the test surface; Test method: After the insulating rubber layer to be tested is 5μm thick, a 55g weight and a flat surface run 300mm (2 circles), the number of points that are not leaked in the test area (a total of 10 points are tested) is recorded in Table 3, and the area of the leaking points is recorded at the same time, so as to calculate the proportion of the area of the non-leaking points in the total area of the test area.
[0202] Evaluation criteria: Under the same pressure, the longer the paper tape passes, the more wear-resistant the aluminum foil is; or the more points of aluminum foil that have not been worn out are tested under the same tape length, the more wear-resistant it is.
[0203] Test of cohesion:
[0204] The adhesive substance is prepared into a slurry and then applied to the carbon-coated layer of the carbon-coated copper foil. After drying, a sample sheet is obtained, one side of the sample sheet is a copper foil surface, and the other side is a glue layer formed by the adhesive substance; the sample sheet is then cut into a sample strip with a size of 2 cm wide and 6 cm long; the copper foil surface of the sample strip is bonded to the surface of the hard substrate (steel plate) with 3M-55230H double-sided adhesive (note that there are no bubbles during the bonding process). The adhesive layer of the fixed sample strip is bonded with 3M-55230H double-sided adhesive, and the copper foil of the same size as the double-sided adhesive is covered on the surface of the double-sided adhesive (note that there are no bubbles during the bonding process). The double-sided adhesive used twice is of the same size to obtain a test sample.
[0205] Manually peel off the copper foil and double-sided adhesive tape at the first end of the test sample in a 180° direction, so that it extends 1 cm beyond the first end of the entire test sample (i.e., the second end). Fix the first end (hard substrate, carbon-coated copper foil, adhesive layer) with a fixture at one end of the tensile testing machine; fix the second end with a fixture at the other end of the tensile testing machine.
[0206] The tensile tester was set to a tensile speed of 50 mm / min and a tensile length of 100 mm for testing. The peel force data obtained in the test is the cohesive force of the coating material. The results are recorded in Table 3.
[0207] Hardness test: The hardness of the surface of the insulating rubber layer was tested using a Shore A hardness tester. The results are recorded in Table 3.
[0208] Adhesion test:
[0209] The above adhesive solutions were respectively scraped onto 13 μm aluminum foil using a 5 μm scraper, and then transferred to a 100° C. oven for drying to prepare the insulating adhesive layer to be tested.
[0210] Use a blade to cut the above-mentioned sample with an insulating adhesive layer of 20mm in width and 100-160mm in length. Stick the special double-sided adhesive NITTO.NO5000NS on the steel plate, with a tape width of 20mm and a length of 90-150mm; fix a paper tape with a width equal to the sample and a length 80-200mm greater than the sample length on the double-sided adhesive, and set a wrinkle adhesive on the paper tape; stick the above-cut fixed-size sample on the wrinkle adhesive, with the insulating adhesive layer facing downward, and then use a 3kg pressure roller to roll the sample surface in the same direction three times to obtain the test sample. Fix the test sample on the test machine, fix the end of the steel plate without the electrode with the lower clamp, fold the paper tape upwards and fix it with the upper clamp, keep the sample axis direction consistent with the force direction, load the test machine at a peeling speed of 10mm / min until the sample breaks, stop the test, record the maximum load force as F (unit N), sample width L = 20mm, calculate the peel strength f1 (unit N / m) according to f1 = F / L, the peel strength is the bonding force. The results are recorded in Table 3.
[0211] Heat resistance test: The TG-DSC technique was used to perform thermogravimetric analysis on the test coating samples, and the thermal decomposition temperatures were recorded in Table 3.
[0212] Table 3
[0213] According to the comparison of the embodiments and the comparative examples, it can be seen that the wear resistance of the insulating adhesive layer formed by the adhesive composition of the present application is significantly better than the wear resistance of the first adhesive 1 or the second adhesive 1 when used alone; and the viscosity of the first adhesive 1 is too large, which is not conducive to construction when used alone and the bonding force is too low; the viscosity of the second adhesive 1 is too small, which affects the construction performance and thus affects the film-forming effect.
[0214] It can be seen from the comparison of Example 2, Examples 4 and 5, and the comparison of Example 1, Examples 6 to 9 that when the content of structural unit B in the first adhesive increases and the content of structural unit C decreases, that is, the content of the hard monomer structural unit of the first adhesive increases, the bonding force of the corresponding adhesive composition decreases.
[0215] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. An adhesive material, comprising an adhesive, wherein: The adhesive comprises structural unit A, structural unit B, structural unit C and structural unit D, and at least part of the structural unit A is cross-linked with at least part of the structural unit D; Wherein, the structural unit A is Wherein, the structural units B are each independently Any one or more of, optionally, the structural unit B is The structural units C are each independently Any one of the above, each m1 and each m2 are independently any integer from 1 to 20, optionally, each m1 is independently any integer from 2 to 12, and each m2 is independently any integer from 8 to 12; The structural units D are each independently Any one or more of n1 is each independently any integer from 1 to 20, optionally, n1 is any integer from 1 to 12, further optionally n1 is any integer from 1 to 6.
2. The adhesive material according to claim 1, wherein At least part of the structural unit A, at least part of the structural unit B, at least part of the structural unit C and at least part of the structural unit D are connected in a chain to form a first chain structure, At least part of the structural unit A, at least part of the structural unit C and at least part of the structural unit D are connected in a chain to form a second chain structure; At least a portion of the structural unit A in the first chain structure is cross-linked with at least a portion of the structural unit D in the second chain structure; At least a portion of the structural unit D in the first chain structure is cross-linked with at least a portion of the structural unit A in the second chain structure.
3. The adhesive material according to claim 1 or 2, wherein The adhesive material satisfies any one or more of the following conditions: 1) The wear resistance of the insulating adhesive layer with a thickness of 3 μm-7 μm formed by the adhesive substance meets the following requirements: tested by an RCA paper tape wear tester, using a 55g weight and a flat tape for 300mm and 2 turns to form a test area, taking n test points in the test area and the spacing between the test points is not less than 2cm, the number of non-leaking points in the test area accounts for more than 30%, where 5≤n≤100, or the area of non-leaking points in the test area is more than 60% of the total area of the test area; 2) The cohesive force of the insulating adhesive layer formed by the adhesive substance is 620N / m-750N / m, and can be 660N / m-725N / m; 3) The Shore hardness of the insulating adhesive layer formed by the adhesive material is 45HA-80HA, and can be 50HA-65HA; 4) The bonding force of the insulating adhesive layer formed by the adhesive substance is 30N / m-90N / m, and can be optionally 40N / m-80N / m.
4. The adhesive material according to any one of claims 1 to 3, wherein In the adhesive, the molar ratio of the structural unit D to the structural unit A is 0.5:1-5:1, optionally 0.5:1-3:1, and further optionally 1:1-3:1; optionally, the molar content of the structural unit A is 4%-50%, optionally 4%-10%, and the molar content of the structural unit D is 1%-50%, optionally 5%-30%, and further optionally 5%-15%.
5. The adhesive material according to any one of claims 1 to 4, wherein In the adhesive, the molar ratio of the structural unit C to the structural unit B is 1:1-300:1, and can be optionally 5:1-50:1; optionally, the molar content of the structural unit B is 0.2%-20%, and can be optionally 1%-5%; optionally, the molar content of the structural unit C is 1%-90%, and can be optionally 55%-90%, and can further be optionally 75%-80%.
6. The adhesive material according to any one of claims 1 to 5, wherein: The adhesive material also includes an insulating filler and / or a dispersant; optionally, the weight ratio of the insulating filler, the adhesive and the dispersant is (70-90):(10-25):0.
4.
7. The adhesive material according to claim 6, wherein The insulating filler includes any one or more of alumina, magnesium oxide, silicon dioxide, titanium dioxide, barium titanate, aluminum nitride, silicon nitride, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, mica, talc, boehmite, zeolite, apatite, kaolin or glass powder; optionally, the volume average particle size D of the insulating filler is V 50≤1μm.
8. The adhesive material according to any one of claims 1 to 7, wherein The adhesive substance further comprises a solvent; optionally, the solid content of the adhesive substance is 20%-40%; Optionally, the solvent of the adhesive substance includes water; Optionally, the viscosity of the adhesive material measured at 25° C. and 12 rpm is 350 mPa·s-900 mPa·s.
9. An adhesive composition comprising an adhesive, wherein: The adhesive comprises a first adhesive and a second adhesive, The first adhesive is a polymer, including structural unit A, structural unit B, structural unit C and structural unit D, The second binder is a polymer, comprising a structural unit A, a structural unit C and a structural unit D, Wherein, the structural unit A is The structural units B are each independently Any one or more of, optionally, the structural unit B is The structural unit C of the first adhesive and the structural unit C of the second adhesive are each independently Each m1 and each m2 is independently any integer from 1 to 20; optionally, each m1 is independently any integer from 2 to 12, and each m2 is independently any integer from 8 to 12; The structural unit D of the first adhesive and the structural unit D of the second adhesive are each independently n1 is each independently any integer from 1 to 20, optionally n1 is each independently any integer from 1 to 12; further optionally n1 is each independently any integer from 1 to 6.
10. The adhesive composition according to claim 9, wherein The weight ratio of the first adhesive to the second adhesive is 1:2.5-1:20, and can be optionally 1:5-1:17.
5.
11. The adhesive composition according to claim 9 or 10, wherein The first adhesive satisfies any one or more of the following conditions: 1) The molar content of the structural unit A in the first adhesive is 5%-30%; 2) The molar content of the structural unit B in the first adhesive is 5%-85%; 3) The molar content of the structural unit C in the first adhesive is 5%-85%; 4) The molar content of the structural unit D in the first adhesive is 5%-15%.
12. The adhesive composition according to any one of claims 9 to 11, wherein The second adhesive satisfies any one or more of the following conditions: 1) The molar content of the structural unit A in the second adhesive is 5%-10%; 2) The molar content of the structural unit C in the second adhesive is 70%-85%; 3) The molar content of the structural unit D in the second adhesive is 5%-20%.
13. The adhesive composition according to any one of claims 9 to 12, wherein The weight average molecular weight of the first adhesive is 500,000-1.5 million; further optionally, the difference between the weight average molecular weights of the first adhesive and the second adhesive is 100,000-1.5 million.
14. The adhesive composition according to any one of claims 9 to 13, wherein The adhesive composition further comprises an insulating filler and / or a dispersant; optionally, the weight ratio of the insulating filler, the adhesive and the dispersant is (70-90):(10-25):0.
4.
15. The adhesive composition according to claim 14, wherein The insulating filler includes any one or more of alumina, magnesium oxide, silicon dioxide, titanium dioxide, barium titanate, aluminum nitride, silicon nitride, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, mica, talc, boehmite, zeolite, apatite, kaolin or glass powder; optionally, the volume average particle size D of the insulating filler is V 50≤1μm.
16. The adhesive composition according to claim 14 or 15, wherein The dispersant includes one or more of polyacrylate compounds, fatty alcohol polyether compounds or polyether-modified siloxane compounds.
17. The adhesive composition according to any one of claims 9 to 16, wherein The adhesive composition further comprises a solvent; optionally, the solid content of the adhesive composition is 20%-40%; further optionally, the solvent of the adhesive composition comprises water.
18. A positive electrode sheet, comprising: A positive electrode current collector (11), wherein at least one side of the positive electrode current collector (11) has a positive electrode film layer region and a hollow foil region; A positive electrode film layer (12), arranged in the positive electrode film layer region of the positive electrode current collector (11); An insulating adhesive layer (13) is arranged in the empty foil area of the positive electrode current collector (11), wherein the insulating adhesive layer (13) is formed by using the adhesive material described in any one of claims 1 to 8, or is formed by curing the adhesive composition described in any one of claims 9 to 17.
19. The positive electrode sheet according to claim 18, wherein: The thickness of the insulating adhesive layer (13) is less than or equal to the thickness of the positive electrode film layer (12). Optionally, the thickness of the insulating adhesive layer (13) is 3 μm-7 μm.
20. A method for preparing a positive electrode sheet, comprising the process of arranging a positive electrode film layer and an insulating adhesive layer on at least one side or both sides of a positive electrode current collector (11), wherein: The process of providing the insulating adhesive layer (13) comprises: Mixing the components of the adhesive substance according to any one of claims 1 to 8 or the adhesive composition according to any one of claims 9 to 17 to form an adhesive solution; Applying the glue solution on the empty foil area of the positive electrode current collector to obtain a preform with the glue solution; The preform with the glue is heated to obtain the insulating glue layer, and the heating temperature is optionally 90°C-120°C.
21. The preparation method according to claim 20, wherein: The process of mixing the components of the adhesive composition to form a slurry comprises: Mixing the dispersant in the adhesive composition with water to form a first dispersion, optionally, the mixing is a first stirring, the first stirring time is 5 min-30 min, and the stirring speed is 200 rpm-400 rpm; Mixing the first dispersion with the insulating filler in the adhesive composition to form a second dispersion, optionally, the mixing is a second stirring, the second stirring time is 30 min-120 min, and the stirring speed is 1200 rpm-1800 rpm; Mixing the second dispersion with the first adhesive in the adhesive composition to form a third dispersion, optionally, the mixing is a third stirring, the third stirring time is 15 min-60 min, and the stirring speed is 400 rpm-700 rpm; The third dispersion is mixed with the second adhesive in the adhesive composition to form the adhesive solution. Optionally, the mixing is a fourth stirring, and the fourth stirring time is 5 min-30 min and the stirring speed is 200 rpm-400 rpm.
22. A secondary battery, comprising a positive electrode sheet, wherein: The positive electrode sheet includes the positive electrode sheet according to claim 18 or 19, or the positive electrode sheet obtained by the preparation method according to claim 20 or 21.
23. An electrical device comprising a secondary battery, wherein: The secondary battery includes the secondary battery according to claim 22.
Citation Information
Patent Citations
Battery binder, lithium ion battery negative electrode plate, and lithium ion battery
CN111500228A
Preparation method of binder resin for edge protection of positive pole piece of lithium battery, binder resin and insulation paste
CN115215962A
Flame retardant adhesive without halogen in use for flexible printed circuit
CN1916101A
Emulsion-type adhesive composition, adhesive sheet obtained therefrom, and method for producing the adhesive sheet
JP2007070448A
Cited By
Adhesion substance, adhesive composition, positive electrode sheet, secondary battery, and electrical apparatus
EP4671337A1